2014
DOI: 10.1002/etc.2457
|View full text |Cite
|
Sign up to set email alerts
|

The occurrence and fate of chemicals of emerging concern in coastal urban rivers receiving discharge of treated municipal wastewater effluent

Abstract: To inform future monitoring and assessment of chemicals of emerging concern (CECs) in coastal urban watersheds, the occurrence and fate of more than 60 pharmaceuticals and personal care products (PPCPs), commercial/household chemicals, current-use pesticides, and hormones were characterized in 2 effluent-dominated rivers in southern California (USA). Water samples were collected during 2 low-flow events at locations above and below the discharge points of water reclamation plants (WRPs) and analyzed using gas … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
58
0
1

Year Published

2015
2015
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 79 publications
(62 citation statements)
references
References 39 publications
3
58
0
1
Order By: Relevance
“…Maximum aqueous concentrations of TCPP, TDCPP, and TCEP for the Santa Clara River watershed were similar to those reported previously in 2 different effluent‐dominated waterways in southern California , indicating similar discharge loading (i.e., loading from the water reclamation plants) for all 3 effluent‐dominated watersheds in the present study region. In contrast, the maximum Santa Clara River concentration for sucralose was 10‐fold higher than was found in other regional watersheds, suggesting that this compound had a correspondingly higher loading into the upper Santa Clara River water reclamation plants relative to the other watersheds .…”
Section: Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…Maximum aqueous concentrations of TCPP, TDCPP, and TCEP for the Santa Clara River watershed were similar to those reported previously in 2 different effluent‐dominated waterways in southern California , indicating similar discharge loading (i.e., loading from the water reclamation plants) for all 3 effluent‐dominated watersheds in the present study region. In contrast, the maximum Santa Clara River concentration for sucralose was 10‐fold higher than was found in other regional watersheds, suggesting that this compound had a correspondingly higher loading into the upper Santa Clara River water reclamation plants relative to the other watersheds .…”
Section: Resultssupporting
confidence: 88%
“…Maximum aqueous concentrations of TCPP, TDCPP, and TCEP for the Santa Clara River watershed were similar to those reported previously in 2 different effluent‐dominated waterways in southern California , indicating similar discharge loading (i.e., loading from the water reclamation plants) for all 3 effluent‐dominated watersheds in the present study region. In contrast, the maximum Santa Clara River concentration for sucralose was 10‐fold higher than was found in other regional watersheds, suggesting that this compound had a correspondingly higher loading into the upper Santa Clara River water reclamation plants relative to the other watersheds . Maximum sediment concentrations of triclocarban in the present study were several fold higher than was reported in Puget Sound (WA, USA; maximum of 17 ng/g dry wt) , but consistent with surface sediment concentrations reported in the vicinity of the marine outfall for a large municipal wastewater treatment plant discharging to the coastal ocean near Los Angeles .…”
Section: Resultssupporting
confidence: 88%
“…Most wastewater treatment plants (WWTPs) are primarily designed to remove nutrients and easily degradable carbon compounds. It has been shown that they have limited capacities to remove pharmaceuticals (Joss et al., 2006), making them major sources of these micropollutants in rivers and streams (Metcalfe et al., 2010, Sengupta et al., 2014). Certain pharmaceuticals, such as antibiotics, are of particular concern since emission may foster the development of resistant pathogens discharged into the aquatic environment (Marti et al., 2014).…”
Section: Introductionmentioning
confidence: 99%
“…In the attempt to identify the main sources of contamination by this insecticide, surveys in North Carolina found that fipronil was present in almost all samples, and concentrations were substantially elevated (10-500 ng/L) near wastewater treatment plant drain pipes (McMahen et al 2016). In Californian watersheds, residues of fipronil and its derivatives in surface water are typically in the range 2-13.8 ng/L (Sengupta et al 2014). A survey of the Santa Clara River (California) found maximum concentrations of pyrethroids (bifenthrin and permethrin), polybrominated diphenyl ethers (PBDEs), and derivatives of fipronil in sediment (from LOQ to 6.8 ppb) that exceeded the threshold levels established for freshwater and estuarine sediments in California, which for fipronil are established as 0.09 and 6.5 ppb dry weight, respectively (Maruya et al 2016).…”
Section: Water and Sedimentsmentioning
confidence: 99%